Deconstruction Santiago’s Class Identity in The Old Man and The Sea - Ariya Tamtama, Rafael Aglis; Sriastuti, Anna (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2025)
In the modern era, social status is often judged based on material possessions, yet this perspective does not always reflect an individual’s true economic condition. Santiago, the protagonist in The Old Man and The Sea, is traditionally perceived as a poor fisherman. However, a deconstructive analysis challenges this notion by revealing contradictions in his social identity. This study aims to analyze Santiago’s class position using Jacques Derrida’s deconstruction approach combined with Karl Marx’s theory of social class. The research employs a qualitative method with textual analysis to examine Santiago’s ambiguous status. The findings indicate that although Santiago appears impoverished, his ownership of fishing tools and freedom over his labor resembles traits of the bourgeoisie rather than the proletariat. Additionally, his resilience and self-perception reflect a level of arrogance, contradicting his supposed humility. The study concludes that Santiago’s character embodies both proletarian and bourgeois elements, demonstrating how class identity is not fixed but fluid and open to multiple interpretations. This analysis highlights the complexity of literary characters and challenges conventional class distinctions through a deconstructive lens.